A LITERATURE REVIEW OF UPDATED ISLAMIC CORPORATE GOVERNANCE ELEMENTS: IMPLICATIONS FOR INDONESIA - Lestari, Irna Puji; Hanafi, Mamduh Mahmadah; Wardhana, Leo Indra (Journal of Islamic Monetary Economics and Finance, 2025)
This study identifies elements of Islamic Corporate Governance (ICG) that contribute to the performance of shariah-compliant firms. A systematic literature review is carried out on 173 relevant articles from the Scopus database, spanning from 2004 to 2024. It identifies five key elements of ICG: (1) Shariah board governance, (2) management and board governance, (3) audit and risk governance, (4) sustainable governance, and (5) Muslim management and board governance. These key elements encompass various sub-elements that have diverse impacts on firm performance across financial, social, and environmental dimensions. The findings offer specific implications for Indonesia, emphasizing the integration of sustainability practices into corporate governance mechanisms and considering distinct approaches to ICG mechanisms for dual-sector performance between Islamic Financial Institutions (IFIs) and non-IFIs. ACKNOWLEDGEMENT The paper is supported by sponsorship from the Indonesia Endowment Fund for Education (LPDP), whose sponsorship has played a crucial role in facilitating the research process. The authors deeply appreciate this support and are grateful for the opportunities it has provided. The authors also gratefully acknowledge the valuable comments provided by the journal's editors and reviewers.